2011
DOI: 10.1039/c1lc00004g
|View full text |Cite
|
Sign up to set email alerts
|

One-step purification of nucleic acid for gene expression analysis via Immiscible Filtration Assisted by Surface Tension (IFAST)

Abstract: The extraction and purification of nucleic acids from complex samples (e.g. blood, biopsied tissue, cultured cells, food) is an essential prerequisite for many applications in biology including genotyping, transcriptional analysis, systems biology, epigenetic analysis, and virus/bacterial detection. In this report, we describe a new process of nucleic acid extraction that utilizes “pinned” aqueous/organic liquid interfaces in microchannels to streamline the extraction mechanism, replacing all washing steps wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
185
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(187 citation statements)
references
References 18 publications
(24 reference statements)
1
185
0
1
Order By: Relevance
“…IP complexes were purified using the IFAST method (illustrated in Fig. 7A) (36). Immune complexes were eluted in the output well in PBS containing 0.01% Tween 20 (17 l).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IP complexes were purified using the IFAST method (illustrated in Fig. 7A) (36). Immune complexes were eluted in the output well in PBS containing 0.01% Tween 20 (17 l).…”
Section: Methodsmentioning
confidence: 99%
“…We suspected it could be better at capturing low affinity and short lived complex components. This technique also dramatically reduces the purification time (36). 4 A scheme is shown in Fig.…”
Section: Exogenous Expression Of Lrp5 or Lrp6 Eliminates Requirementsmentioning
confidence: 99%
“…In a recent report of a 96-well plate mRNA extraction assay analogous to our continuous tubing design, Berry et al use low concentrations of Triton X-100 to reduce the interfacial tension at the solution/valve interface. 13 The group reported that the addition of 0.01-0.1% Triton X-100 did not interfere with the mRNA binding chemistry yet facilitated the magnetic transfer of the beads across the immiscible phase.…”
Section: Resultsmentioning
confidence: 99%
“…This inverted solid phase format based on magnetic beads and stationary fluids separated by surface tension forces has been developed for a number of applications. [11][12][13][14][15] Other laboratory-based magnetic bead assays, such as enzyme-linked immunosorbent assays (ELISAs) or onbead isothermal polymerase chain reaction (PCR), could potentially benefit from the simplicity and flexibility of this format for applications in low-FIG. 1.…”
Section: Introductionmentioning
confidence: 99%
“…A disadvantage is that it takes about 4 h to run. A similar idea not currently in a product is that NA-bound beads could be moved through an immiscible liquid wash phase to remove contaminants (70 ).…”
Section: Selecting From Current Methodsmentioning
confidence: 99%